Correlation of the Plasma Concentration of Eltrombopag With Efficacy in the Treatment of Refractory Aplastic Anemia: A Single-Centre Study in China - Zuo, Wei; Zhang, Bo; Ruan, Jing; Chen, Miao; Han, Bing (Frontiers in Pharmacology, 2020)
Background and purpose: Eltrombopag (ELT) was effective in the treatment of relapse/refractory aplastic anemia (AA) patients. Response and adverse drug reaction (ADR) differed greatly among individuals even at the same dosage of ELT. Methods: Patients diagnosed with non-severe aplastic anemia (NSAA) between January 2018 to January 2019 in Peking Union Medical Colleague Hospital who were refractory to immunosuppressive therapy were treated with ELT and followed up for at least 6 months. Plasma concentrations of ELT were detected by the high-performance liquid chromatography-mass spectrometry after at least two months of ELT treatment and staying for that dosage for at least two weeks. Dose-concentration, concentration-response and concentration- ADR relation were evaluated. Results: Among the 72 patients treated with ELT during that period, 44 patients with complete data were enrolled. 6 (13.6%) were males and 38 were females (86.4%) with a median age of 54 years (IQR: 38.5-63). By the time of plasma concentration detected, the median dosage of ELT was 75(IQR 50-100) mg/d and median time for total ELT exposure was 3 (IQR 2.0-6.0) months, and 37 (70.5%) patients responded to ELT. The median concentration of ELT was 10.4μg/ml (IQR 3.7-24.4μg/ml). The concentration of ELT was positively correlated with the daily dose of ELT (r = 0.68, p < 0.001). Multivariate logistic regression analysis showed that the risk of inefficacy of ELT with a concentration between 11.2-15.2 μg/ml was 0.028-fold (95% CI: 0.001-0.864; P=0.041) to those with a concentration between 3.2-7.2μg/ml. The cutoff value of concentration for ELT efficacy was 12.50μg/ml by receiver operation characteristic curve. A higher risk of ADR was related to a longer total exposure to ELT (P=0.012). Although not significant, odd ratio (OR) increased with ELT concentration, suggesting a possible elevated risk of ADR correlated with blood concentration. Conclusions: ELT is effective for the treatment of NSAA with accepTable side effects. Plasma concentration of ELT correlated with the dose and the effects of ELT.